Emerging chitosan-essential oil films and coatings for food preservation - A review of advances and applications. (1st December 2021) - Zhang, Xinhui; Ismail, Balarabe B.; Cheng, Huan; Jin, Tony Z.; Qian, Mengyan; Arabi, Saifanassour Ali; Liu, Donghong; Guo, Mingming
Abstract: With the rising demand for fresh and ready-to-eat foods, antimicrobial packaging has been developed to control or prevent microbial growth as well as maintain food quality and safety. Chitosan is an advanced biomaterial for antimicrobial packaging to meet the growing needs of safe and biodegradable packaging. The application of natural essential oils as antimicrobial agents effectively controls the growth of spoilage and pathogenic microbes. Thus, chitosan edible coatings and films incorporated with essential oils have expanded the general applications of antimicrobial packaging in food products. This review summarized the effect of essential oils on modifying the physicochemical characteristics of chitosan-based films. Notably, the antimicrobial efficacy of the developed composite films or coatings was highlighted. The advances in the preparation methods and application of chitosan films were also discussed. Broadly, this review will promote the potential applications of chitosan-essential oils composite films or coatings in antimicrobial packaging for food preservation. Graphical abstract: Unlabelled Image Highlights: This review presented advances in chitosan films containing essential oils (EOs). Various methods for the preparation of chitosan films were discussed. EOs can modify the physical and mechanical properties of chitosan films. Chitosan films incorporated with EOs exhibited enhanced antimicrobial activity. These films or coatings have potential applications in extending food shelf-life.